2010
DOI: 10.1117/12.842957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatments/coatings and soft bake profile on surface uniformity and adhesion of SU-8 on a glass substrate

Abstract: We present the effect of surface treatments/coatings and soft bake temperatures aimed at improving adhesion and surface uniformity of SU-8 on glass substrates. While the adhesion strength of SU-8 to metal layers on glass and silicon has been previously investigated, our research examines the influence of additional surface treatments (RCA, Acetone/IPA rinse) and coatings (fresh/one-day-aged Ti, fresh/one-day-aged Cr, SU-8 2005®) on adhesion strength as well as surface uniformity for 100 μm thick SU-8 films. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Cells in traps featuring Cr adhesion layers did not survive, but remained viable in all other traps. Fortunately, we have also shown that SU-8 adheres more strongly to Ti than Cr [30].…”
Section: Testing Of Fabricated Hydrodynamic Cell Trap Arraysmentioning
confidence: 59%
“…Cells in traps featuring Cr adhesion layers did not survive, but remained viable in all other traps. Fortunately, we have also shown that SU-8 adheres more strongly to Ti than Cr [30].…”
Section: Testing Of Fabricated Hydrodynamic Cell Trap Arraysmentioning
confidence: 59%